Sleep duration and sleep loss during pregnancy: a longitudinal FinnBrain birth cohort study - Aukia, Linda; Paavonen, E. Juulia; Karlsson, Linnea; Pelto, Juho; Perasto, Laura; Karlsson, Hasse; Polo-Kantola, Paivi (SPRINGER HEIDELBERG, 2026)
Purpose To investigate sleep duration and sleep loss during antenatal period and assess associative factors, including maternal characteristic and mood symptoms.
Methods A cohort of 3038 women was enrolled. Self-reported sleep duration and sleep loss, the latter being calculated from preferred sleep need and actual sleep duration, were measured in early, mid- and late pregnancy, and at delivery. The associations with age, BMI, parity, education, smoking, napping, and depressive and anxiety symptoms were evaluated.
Results Sleep duration was longest in early pregnancy and shortest at delivery (7.93 h-7.76 h, p < 0.001). The proportion of short sleepers (< 6 h) increased from 1.4% to 5.9% throughout the studied period (p < 0.001). Mean sleep loss remained stable in early- and mid-pregnancy, lowering in late pregnancy (p < 0.001) and increasing again until delivery (p = 0.003). The number of women with notable sleep loss (> 2 h) was similar during the first three measurement points (9.4%, 8.9% and 9.5%), but increased until delivery (14.1%, p < 0.001). Older, multiparous, and more-depressive women slept less (p < 0.001, p < 0.001, p = 0.017). Women with higher BMI were more likely to sleep < 6 h in late pregnancy (p = 0.012). Multiparous, more-depressive, and higher-BMI women reported more sleep loss (p < 0.001, p < 0.001, p = 0.049).
Conclusion We confirmed earlier reported decrease in sleep duration at the end of pregnancy. As a novel finding, we showed a notable increase in sleep loss during the last month of pregnancy. Various factors were associated with both short sleep and sleep loss, especially multiparity, napping and depressive symptoms.